Amidoboranes of rubidium and caesium: the last missing members of the alkali metal amidoborane family. Issue 46 (16th November 2017) - Owarzany, Rafał; Jaroń, Tomasz; Leszczyński, Piotr J.; Fijalkowski, Karol J.; Grochala, Wojciech
Abstract : The nature of temperature-induced phase transitions of rubidium and caesium amidoboranes was elucidated using structural and spectroscopic methods. Abstract : We report the synthesis and physicochemical characterization of two ammonia borane derivatives: rubidium amidoborane (RbNH2 BH3 ) and caesium amidoborane (CsNH2 BH3 ). Both compounds undergo solid–solid phase transition upon heating and then evolve pure hydrogen at temperatures lower than 125 °C. The phase transition is clearly seen in the Raman spectra. We present crystal structures of both low- and high-temperature forms of the title compounds which were solved from powder X-ray data.